Electric and Scalar Charged Fluid Sphere in General Relativity: Interior solutions of an electric and scalar charged fluid sphere (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper provides interior solution of an electric and scalar charged fluid sphere in general relativity under certain assumptions.